REVIEW ON TRADITIONAL AND ADVANCE USE OF MORINGA OLEIFERA AS FOOD AND MEDICINE (International Association of Biologicals and Computational Digest, 2023)
The review aimed to highlight the Moringa oleifera plants uses traditional to advance uses of Moringa and how to improve nutritional value in daily edible product. Moringa dried leaves use different recipe and value added food using Moringa leaf. M. oleifera is used to treat a variety of conditions, including diabetes, hypertension, stress, skin, cancer, and many others. They can be consumed fresh or dried. Moringa all part is edible like leaves, fruits, root and bark. From leaves of M. oleifera the product are prepare like chocolate, paneer, biscuit, cake, yogurt, khakhara, chin-chin, muffins. The study shown some interesting information provides a breakdown of the findings regarding the usage of the Moringa species in Nigeria by ethnicity as well as the applications of Moringa oleifera in different food recipe improves their nutritional and functional value.
Keywords: Moringa oleifera, Nutritional value, edible products, traditional use